The sulfur of the soils and their possible influncioa in tuberculosis and the repilo of the olive trees - Pérez Miranda, C.; Callao, V.; Romero, P. (Ars Pharmaceutica (Internet), 1970)
In this work, a study of the possible influence of soil sulfur on tuberculosis and olive tree repilo is made.The results obtained in the total sulfur determinations of the leaves and in the quantitative assessment of sulfo-oxidant and sulphate-reducing activities of the soils are exposed.